Menyikapi Folklor Baremah Adat Binua Dait Dalam Terang Gaudium Et Spes Art. 40 - Jakarias; Dedi, Apolonaris (Perspektif, 2024)
This study examines the tradition of Baremah Adat Binua Dait of the Dayak tribe in Bareh Hamlet, West Kalimantan, as well as its integration with Catholic teachings in the context of Gaudium et Spes Art. 40. The background of this research began with the interaction between local culture and Catholicism among the Dayak people, who have long followed the Baremah tradition as part of their cultural identity. The issue raised is how elements of Baremah culture are adapted within the framework of the Catholic faith, especially in the perspective of the inculturation stated in the Gaudium et Spes document. The purpose of this research is to understand the process of syncretism that occurs between the Dayak tradition and Catholicism. The method used is a qualitative approach with interviews, observations, and documentation analysis. The results of the study show that various aspects of the Baremah tradition have been adapted to Catholic teachings, such as the use of the term "Jubata" which is recognized as God in the Catholic context. This process reflects the dynamics of syncretism that includes dialogue and adaptation between local culture and religious teachings. This research provides insight into how cultural identity can be maintained in the context of new religions, as well as the impact of syncretism on the religious experience of the Dayak community.